FROM SPECTATOR TO “SPECTACTOR” - Penn, Claire; Watermeyer, Jennifer; Barratt, Joanne (PINS-Psychology in Society, 2025)
Buckland, A (photographs), McDougall, K, Swartz, L & van der Merwe, A (2006) Zip zip my brain harts. Cape Town: HSRC Press. ISBN 0-7969-2159-8 pbk. Pages xi + 91. This is an unexpected, creative and delightful book filled with interesting and relevant information pertaining to living with disability. It aims to portray disability as ordinary and everyday, and through the use of challenging photographs sheds an understanding on societal and medical approaches to disability and on the human tendency to be “thrilled” by the extraordinary.